SMART PERPUSTAKAAN: INOVASI PENINGKATAN LITERASI SEKOLAH ANAK USIA DINI AKAR TUMBUH MELATI DI KELURAHAN SENDANGADI MLATI SLEMAN - Aris Wahyu Murdiyanto; Kartikadyota Kusumaningtyas; Ikbal Rizki Putra; Septiyati Purwandari; Bara Falah Adikaputra; Agung Satria Panca; Fitriatul Hasanah (Jurnal Berdaya Mandiri, 2024)
This program aims to enhance educational services and literacy knowledge among early childhood students at Akar Tumbuh Melati School through the implementation of appropriate technology (Smart Perpustakaan). The activities were carried out in five stages: socialization, training, technology implementation, assistance, and evaluation with sustainability measures. The Smart Perpustakaan technology includes a library space, an encyclopedia book collection, virtual reality (VR) videos for interactive reading activities, and Cardboard VR devices. The results show a 92% increase in digital literacy knowledge and a 33.33% improvement in the quality of educational services. This program successfully reduced children's dependency on non-educational digital content and opened opportunities for sustainable collaboration with related stakeholders. Keyword: early childhood literacy, educational services, appropriate technology, Smart Library, community service